KEBIJAKAN PROGRAM LITERASI DINI - Novan Ardy Wiyani (Institut Agama Islam Negeri (IAIN) Palopo, 2022)
Indonesia is currently experiencing a literacy crisis both among the general public and among students. To overcome the literacy crisis, the government then promoted the School Literacy Movement from elementary to high school levels. Basically, the School Literacy Movement must also be implemented at the PAUD level, such as in kindergarten. This is because there are demands from parents that their children have early reading skills as a provision for entering the 1st grade of elementary school. This then made TK Pertiwi II Cikembulan formulate and implement policies for early literacy programs. This study aims to describe and analyze the implementation of early literacy program policies in TK Pertiwi II Cikembulan. This research is a qualitative research with the type of case study research. Data were collected by interview, observation and documentation and then analyzed using Miles and Huberman model data analysis techniques. The results showed that the policy of the early literacy program at TK Pertiwi II Cikembulan was motivated by the desire of parents to have their children have early literacy skills. Then the results showed that the policy of early literacy program at TK Pertiwi II Cikembulan was implemented through four activities. First, play activities contain early literacy. Second, read load activities. Third, early literacy habituation activities in schools. Fourth, early literacy habituation activities at home. These four can be implemented well because of the democratic leadership of the head of the Cikembulan TK Pertiwi II and the awareness of the teachers that they are learner society.